Analisis Pemecahan Masalah Matematis Siswa Soal Kontekstual AKM Ditinjau dari Tahap Polya - Putri, Fitria Afifah Aliya; Nurcahyo, Adi; Faiziyah, Nuqthy (Paedagogie, 2026)
The capability to tackle math challenges plays a crucial role in applying the Independent Curriculum. This skill is essential for addressing practical issues derived from the Minimum Competency Assessment (AKM) to evaluate numeracy skills. This research aims to understand students' abilities when solving mathematics problems based on AKM-based contextual questions. This research uses qualitative descriptive types. This study involved 32 students in class VIII B SMP Muhammadiyah PK Kottabarat Surakarta, who were chosen using the purposive sampling technique. The data gathering was done through AKM-related problem-solving inquiries Furthermore, the data is analyzed through three stages, namely decomposition, presentation, and withdrawal of results. Data was analyzed by grouping students' solving abilities based on average results and standard deviations into high, medium and low level. Students who are in a high level can complete all stages in the problem-solving process, such as Understanding problems, Divising a plan, Carrying out the plan strategies, and Evaluating results. On the other hand, students with a moderate level can complete three of the four stages of Polya, namely understanding problems, developing strategies, and implementing plans. Meanwhile, students at the lower level only managed to meet one of the four indicators, namely the stage of understanding the problem.